Liraglutide Attenuates Non-Alcoholic Fatty Liver Disease in Mice by Regulating the Local Renin-Angiotensin System - Mengying Yang; Xiaoyi Ma; Xiuping Xuan; Hongjun Deng; Qi Chen; Li Yuan (Frontiers Media S.A., 2020)
The renin-angiotensin system (RAS) is involved in the pathogenesis of non-alcoholic fatty liver disease (NAFLD) and represents a potential therapeutic target for NAFLD. Glucagon-like peptide-1 (GLP-1) signaling has been shown to regulate the RAS within various local tissues. In this study, we aimed to investigate the functional relationship between GLP-1 and the local RAS in the liver during NAFLD. Wild-type and ACE2 knockout mice were used to establish a high-fat-induced NAFLD model. After the mice were treated with liraglutide (a GLP-1 analogue) for 4 weeks, the key RAS component genes were up-regulated in the liver of NAFLD mice. Liraglutide treatment regulated the RAS balance, preventing a reduction in fatty acid oxidation gene expression and increasing gluconeogenesis and the expression of inflammation-related genes caused by NAFLD, which were impaired in ACE2 knockout mice. Liraglutide-treated HepG2 cells exhibited activation of the ACE2/Ang1-7/Mas axis, increased fatty acid oxidation gene expression, and decreased inflammation, which could be reversed by A779 and AngII. These results indicate that the local RAS in the liver becomes overactivated in response to NAFLD. Moreover, ACE2 knockout increases the severity of liver steatosis. Liraglutide has a negative and antagonistic effect on the ACE/AngII/AT1R axis, a positive impact on the ACE2/Ang1-7/Mas axis, and is mediated through the PI3K/AKT pathway. This may represent a potential new mechanism by which liraglutide improves NAFLD.